Effect of nitrogen application and planting density on grain yield and quality of japonica rice cultivar D46 in the planting area of Chengdu plain - LAN Yan; HUANG Peng; JIANG Guchihong; LEI Xiaobo; DING Chunbang; LI Tian (浙江大学学报. 农业与生命科学版)
Rice is one of the most important crops in the world, especially in Asia, where more than 90% of the world’s rice is grown and consumed. In recent years, with the increase of living quality, the requirement for rice improvement is not only limited to yield, but also to its quality. During rice development, genetic and environmental factors significantly affect both of the yield and quality. Among the environmental factors, fertilizer management and planting density are considered as the main factors affecting rice growth and development. Data from the previous studies on the impact of nitrogen application rate and planting density on rice yield and quality have been inconsistent due to the differences in regional ecological conditions. Therefore, it is necessary to continue exploring the influence of nitrogen application rate and planting density on rice yield and quality.Chengdu plain, the main rice cropping region in the southwest of China, has the unique light, heat and water resources. In order to promote the planting of a japonica rice variety (identified in our previous research) in this area, we investigated how nitrogen (N) application rate and planting density and their interactions affect grain yield and quality. Data from this study would provide information for japonica rice cultivation in the area for high yield and good quality.To investigate the effect of nitrogen application rate and planting density on rice grain yield and quality characteristics, we used japonica rice cultivar D46 as the test material in this study. Split plot experiments with N application rate (N 150,225 and 300 kg/hm2) as main plot and planting density (20×104, 26.67×104 and 40×104 seedlings/hm2) as sub-plot were carried out. The experiment was conducted on sandy loam in 2013 at the experimental farm of Sichuan Agricultural University in Wenjiang, China.The results showed that both N application rate and planting density had significant effects on the yield of the japonica rice cultivar D46 (P<0.05). The combination of N application rate of 225 kg/hm2 and planting density of 26.67×104 seedlings/hm2 led to the highest yield (7.58×103 kg/hm2), and which was significantly higher than other treatments (P<0.05). Dry matter accumulation tended to increase with the increase of N application rate during the whole growth period, whereas, for planting density, it reached the maximum at 26.67×104 seedlings/hm2 rather than at 20×104 and 40×104 seedlings/hm2. Furthermore, N application rate and planting density were shown to have different degrees of influence on the rice quality. The processing quality, chalky rate and protein content increased as the N application increased from 150 to 225 kg/hm2 and then declined with any further increases in N supply. In contrast, increasing planting density was not conducive to improving rice quality.Based on the results, and considering the importance of improving both rice yield and quality, the optimal combination of N application rate and planting density for japonica rice cultivar D46 in the planting area of Chengdu plain is N 225 kg/hm2 and 26.67×104 seedlings/hm2, respectively.